A novel troponin T peptide in humans: Assay, biochemistry and preliminary findings in acute coronary syndromes. (1st July 2015) - Lee, J.; Young, J.; Frampton, C.M.; Aldous, S.; Troughton, R.W.; Than, M.; Richards, A.M.; Pemberton, C.J.
Abstract: Introduction: High sensitivity assays for cardiac troponin (cTn) have reduced time to diagnosis of myocardial infarction (MI) but at costs to diagnostic specificity. We hypothesised that measurement of an upstream open reading frame peptide (uORF) from the human cTnT gene (TnTuORF) might improve cTn specificity in MI patients. Methods: A novel immunoassay to TnTuORF was developed and used to document circulating concentrations in normal healthy volunteers (n = 150); assess potential trans-organ secretion in patients undergoing cardiac catheterisation (n = 16); characterise temporal TnTuORF concentrations during ST-elevation MI (STEMI, n = 4) and assess the potential of TnTuORF to assist the diagnosis and prognosis of MI in patients presenting with chest pain suspicious of ACS (n = 502). Plasma immunoreactive TnTuORF was characterised on reverse phase and size exclusion HPLC. Results: In normal volunteers and suspected acute coronary syndrome (ACS) patients, TnTuORF had no relationship with TnI or TnT. Trans-organ venous sampling suggested TnTuORF secretion is not exclusively cardiac based. In STEMI patients, TnTuORF concentrations decreased for up to 12 h after onset. In suspected ACS patients, TnTuORF could not diagnose MI (ROC AUC = 0.446, P = 0.117) but could diagnose cardiac disorders other than MI (AUC = 0.79, P < 0.001). Conclusion: This is the first evidence for a circulating uORF peptide. TnTuORF does not appear to aid the diagnosis of MI but further studies to assess its potential in cardiovascular disease are required.